2019
DOI: 10.1016/j.alcohol.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Low cognitive flexibility as a risk for heavy alcohol drinking in non-human primates

Abstract: Chronic alcohol abuse is frequently considered a habitual or inflexible behavior; however, measures of pre-existing cognitive flexibility prior to initiation of alcohol use are usually not available. This study used rhesus monkeys and an attentional set-shifting task to investigate whether pre-existing cognitive flexibility would predict increased risk for heavy alcohol drinking. As previously reported, monkeys were given 30 daily set-shifting sessions prior to alcohol access. These sessions consisted of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 55 publications
8
43
0
Order By: Relevance
“…The low and binge drinkers were collapsed into a group of non-HDs (NHDs; n = 19), and heavy and very heavy drinkers were grouped as HDs ( n = 26). This parallels previous work in humans (Squeglia et al, 2015) and in nonhuman primates (Cervera-Juanes et al, 2017; Shnitko et al, 2019). The third linear mixed model (LMM 3.1) used the categorical variable (group) to determine how heavy and nonheavy alcohol drinking affects age-related changes in volume of the brain, white matter, and gray matter.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…The low and binge drinkers were collapsed into a group of non-HDs (NHDs; n = 19), and heavy and very heavy drinkers were grouped as HDs ( n = 26). This parallels previous work in humans (Squeglia et al, 2015) and in nonhuman primates (Cervera-Juanes et al, 2017; Shnitko et al, 2019). The third linear mixed model (LMM 3.1) used the categorical variable (group) to determine how heavy and nonheavy alcohol drinking affects age-related changes in volume of the brain, white matter, and gray matter.…”
Section: Methodssupporting
confidence: 89%
“…Rhesus macaques have been widely used as a translational model for investigating the neural substrates of human behavior and, particularly, alcohol use and abuse (Grant and Bennett, 2003; Wright and Taffe, 2014; Chandler et al, 2017; Shnitko et al, 2019; Thomas and Czoty, 2019). The present longitudinal study was focused on the measurement of brain changes that occur during late adolescence and early adulthood in rhesus monkeys (3.5–7.5 years of age) because this stage of development confers maximum risk for heavy drinking in humans and macaques (Helms et al, 2014; Substance Abuse and Mental Health Services Administration, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, regular binge-drinking does not only increase the likelihood and frequency of hangover, it also strongly increases the risk of developing alcohol use disorder (AUD) [13,14,15]. While it is still unclear whether or how these two consequences are functionally linked, it has been shown that the acute cognitive effects of a high-dose alcohol intoxication resemble the pattern of cognitive deficits observed in AUD patients—both produce pronounced impairments in cognitive control/executive functioning, while behavioural automaticity is comparatively preserved [16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Reversals of the correct stimulus were imposed after reaching criteria for acquisition of the discrimination, providing an opportunity to measure an individual's ability to alter their response strategies (i.e., demonstrate cognitive flexibility). Performance on the task predicted future heavy alcohol consumption in rhesus macaques (Shnitko et al, ) and suggests that a reduced ability to optimize behavior when contingencies change is a predisposing factor to heavy drinking. To extend these results, the present study is focused on the consequences of chronic alcohol drinking on behavioral flexibility in this same cohort of rhesus monkeys.…”
mentioning
confidence: 99%
“…Cognitive and sensory‐motor domains of behavioral flexibility were assessed with the SST. In this longitudinal design, first retention of the SST was measured (Shnitko et al, ), and then, a sensory‐motor challenge to the SST was assessed by decreasing the size of the visual stimuli. A similar approach has been used in human subjects where recognition of visual shapes was influenced by the size of the shapes presented (Jolicoeur, ).…”
mentioning
confidence: 99%